Factors Affecting The Survival Trend In Carcinoma Stomach- A Hospital Based Study (TAJ: Journal of Teachers Association, 2018)
Stomach cancer is a gastrointestinal malignancy with insidious onset and poor prognosis. The disease predominantly affects the older age groups with pick incidence between 60 to 70 years of age. The total number of stomach cancer patients available for the study within the stipulated time was 105. Among them 69.52% patients were male and 30.48% patients were female. 0.95% patient belonged to age group 70 years of age. Mean age was 54.91 years ± 13.42 SD. In our study, 45.6% survived 24 months. Among 57 expired patients, 14 got curative treatment and rest of 43 got palliative treatment. Those who got curative treatment, 36.4% survived 10–12 months, 45.5% 13–24 months and 18.1% > 24 months. Those who got palliative treatment 51.5% survived